2014
DOI: 10.18388/abp.2014_1846
|View full text |Cite
|
Sign up to set email alerts
|

Antimutagenic effects of aqueous fraction of Myristica fragrans (Houtt.) leaves on Salmonella typhimurium and Mus musculus.

Abstract: Natural plant extracts offer a promising hope in the prevention/treatment of cancer arising from genetic mutations. This study evaluated in vitro and in vivo mutagenic and antimutagenic effects of aqueous fraction of Myristica fragrans (AFMF) leaves on TA100 strain of Salmonella typhimurium and Mus musculus (Male Swiss albino mice), respectively. The antioxidant activity of AFMF against 2,2-diphenyl-1-picrylhydrazyl (DPPH), total phenolic and flavonoid contents were determined, followed by its phytochemical el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 41 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…However, most of these studies were considered not relevant, as they were performed with a different test item, i.e. nutmeg seed soaked in distilled water (Alabi et al., 2016), methanolic leaf extract (Akinboro et al., 2014), ethanolic nutmeg seed extract (Mahmoud et al., 1992). Only one study investigated the genotoxicity of nutmeg oil (commercial sample, further details not mentioned) in vitro in an Ames test and a chromosomal aberration test.…”
Section: Assessmentmentioning
confidence: 99%
“…However, most of these studies were considered not relevant, as they were performed with a different test item, i.e. nutmeg seed soaked in distilled water (Alabi et al., 2016), methanolic leaf extract (Akinboro et al., 2014), ethanolic nutmeg seed extract (Mahmoud et al., 1992). Only one study investigated the genotoxicity of nutmeg oil (commercial sample, further details not mentioned) in vitro in an Ames test and a chromosomal aberration test.…”
Section: Assessmentmentioning
confidence: 99%
“…Further preparations of the slides were done as previously described (Akinboro & Bakare, 2007;Çavuşoğlu et al, 2016;Priyanka et al, 2019. Five slides were observed for the stages of mitosis and chromosomal aberrations induced by each dose of A. vera gel extract in combination with sodium azide (Akinboro et al, 2012;Akinboro et al, 2014;Akinboro et al, 2016). The remaining six onions were suspended in freshly prepared Aloe vera gel extract for another 24 hour root growth.…”
Section: Allium Cepa Assaymentioning
confidence: 99%
“…Nutmeg fruits are used as herbal medicines and spices for the treatment of abdominal pain, diarrhea, oral mucosal diseases, joint pain, and insomnia. Modern scientific research has shown that nutmeg fruits possess various pharmacological activities, including antiinflammatory, antibacterial, analgesic, anti-anxiety, liver function improvement, and anti-mutagenic properties [30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%